The dynamics of global dominance : European overseas empires, 1415-1980 - Abernethy, David B. (Yale University Press, 2000)
"In advancing a theory of imperialism that includes European and non-European actors, and in analyzing economic, social, and cultural as well as political dimensions of empire, Abernethy helps account for Europe's long occupation of global center stage. He also sheds light on key features of today's postcolonial world and on the legacies of empire, concluding with an insightful approach to the moral evaluation of colonialism."--Provided by publisher.